An Analysis of Students’ Ability in Writing Analytical Exposition Text - Reski Reski; Nurhaspia Nurhaspia; Uswatunnisa Uswatunnisa; Rabiatul Adawiah (LETS: Journal of Linguistics and English Teaching Studies, 2021)
This study aims to determine the ability to write an English analytical exposition text in class XI Religion 2 MAN 2 Polewali. Therefore, the main problem is how the students' ability to write analytical exposition texts in class XI Agama 2. This research is quantitative and descriptive. The population in this study were students of class XI Religion 2 MAN Polewali. This means that the population is 15 students, and this population is used as a sample of 15 students. In collecting the data, the researcher used a writing test. Students are asked to make an analytical exposition text. Analysis of student score data found that students' ability in writing analytical exposition texts was still lacking in class XI (15 students). In this case, in class XI, Religion 2, there were no students who got very good scores. Six students got the same student's work. The results of this study indicate that the ability to write analytical exposition texts is not capable with students' writing results below the average, and the researchers also found that students' writing results are considered impure because of the indications that students take them from the internet. This is indicated by the use of vocabulary used in addition to the results of interviews with the teacher. The researcher found that there was no guidance from the teacher to the students on how to write analytically. The teacher's exposition text only directs students to look for the structure of the analytical exposition text.